2000
DOI: 10.1161/01.cir.101.18.2149
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Tumor Necrosis Factor-α and Increased Risk of Recurrent Coronary Events After Myocardial Infarction

Abstract: MD; for the Cholesterol And Recurrent Events (CARE) InvestigatorsBackground-Levels of tumor necrosis factor-␣ (TNF-␣) increase with acute ischemia. However, whether elevations of TNF-␣ in the stable phase after myocardial ischemia (MI) are associated with increased risk of recurrent coronary events is unknown. Methods and Results-A nested case-control design was used to compare TNF-␣ levels obtained an average of 8.9 months after initial MI among 272 participants in the Cholesterol And Recurrent Events (CARE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
482
2
29

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 859 publications
(525 citation statements)
references
References 38 publications
12
482
2
29
Order By: Relevance
“…6,7 Previous clinical studies have indicated the presence of activated circulating leukocytes and inflammatory cytokines, as well as acute-phase reactants such as CRP in patients with AMI. 13,14,19 In particular, it has been shown that elevated CRP levels and monocytosis are associated with LV enlargement and aneurysm after reperfused MI, suggesting an important role of inflammatory response in post-infarct remodeling. 8,9 The monocyte-related cytokines, such as IL-6, stimulate liver cells to produce CRP and lead to peripheral monocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Previous clinical studies have indicated the presence of activated circulating leukocytes and inflammatory cytokines, as well as acute-phase reactants such as CRP in patients with AMI. 13,14,19 In particular, it has been shown that elevated CRP levels and monocytosis are associated with LV enlargement and aneurysm after reperfused MI, suggesting an important role of inflammatory response in post-infarct remodeling. 8,9 The monocyte-related cytokines, such as IL-6, stimulate liver cells to produce CRP and lead to peripheral monocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In addition, clinical studies have demonstrated the presence of increased circulating levels of proinflammatory cytokines in patients with AMI. 13,14 These cytokines can stimulate fibroblast proliferation and collagen deposition and may be involved in apoptosis, which is proposed as an important mechanism in postinfarct remodeling. 15,16 In view of these results, it is apparent that proinflammatory cytokines play an important role in the reperfused myocardium during the remodeling process.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism might be mediated by cytokines such as interleukin-6 [26] and tumor necrosis factor α [27,28]. Our recent experimental studies have shown a profound and diffuse impairment of endothelial function of coronary vascular bed during acute C. pneumoniae infection in piglets [23].…”
Section: Mechanism Of Infection Initiated Chdmentioning
confidence: 99%
“…protein (CRP), interleukin-6 (IL-6), tumour necrosis factor-alpha and markers of endothelial dysfunction have been shown to be independent predictors of both diabetes and cardiovascular risk (6,(8)(9)(10). Furthermore, inhibition of fibrinolysis, which is attributable to elevated concentrations of plasminogen activator inhibitor type 1 (PAI-1), is associated with insulin resistance and type 2 diabetes, and predicts myocardial infarction and stroke (11,12).…”
mentioning
confidence: 99%